Analisis Kesesuaian Honor dan Hak-Hak KPPS dengan Peraturan Desa serta Undang-Undang Ketenagakerjaan di Indonesia - Lola Ledy Melia Dina (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Elections are an important pillar in a democratic system, and the Polling Organizer Group (KPPS) plays a strategic role in the process. However, high workloads, inadequate honorariums, and inadequate protection of rights are often the main problems faced by KPPS, especially in the 2024 Simultaneous Elections. This study aims to analyze the conformity of KPPS honorariums and rights with applicable village regulations and labor regulations, and to provide recommendations to improve the welfare and protection of KPPS. The research method used is a qualitative approach with data collection through in-depth interviews and direct observation. Research informants involved KPPS members, village officials, and other stakeholders. The collected data were analyzed descriptively to provide an in-depth understanding of the working conditions and rights of KPPS in the implementation of the 2024 Simultaneous Elections. The results of the study showed that the KPPS workload was very high, with working hours reaching more than 12 hours a day without adequate rest. This risks increasing physical and mental fatigue, as well as errors in carrying out tasks. In addition, the honorarium received by KPPS often does not reflect their workload, with several cases of non-transparent honorarium deductions by village officials. Protection of basic rights such as social and health security has also not been optimally fulfilled. The unclear legal status and lack of understanding of KPPS rights have led to low community participation in elections. This study recommends the need for stricter regulations regarding the management of KPPS honorariums, increased supervision at the village level, and intensive training to improve the efficiency and welfare of KPPS members. Increasing transparency in the management of honorariums and the provision of basic rights is also important to support the implementation of fair and quality elections in Indonesia.